Variation in propofol induction doses administered to surgical patients over age 65. Issue 8 (31st March 2021) - Schonberger, Robert B.; Bardia, Amit; Dai, Feng; Michel, George; Yanez, David; Curtis, Jeptha P.; Vaughn, Michelle T.; Burg, Matthew M.; Mathis, Michael; Kheterpal, Sachin; Akhtar, Shamsuddin; Shah, Nirav
Abstract: Background/Objectives: Advanced age is associated with increased susceptibility to acute adverse effects of propofol. The present study aimed to describe patterns of propofol dosing for induction of general anesthesia before endotracheal intubation in a nationwide sample of older adults presenting for surgery. Design: Retrospective observational study using the Multicenter Perioperative Outcomes Group data set. Setting: Thirty‐six institutions across the United States. Participants: A total of 350, 766 patients aged over 65 years who received propofol for general anesthetic induction and endotracheal intubation between 2014 and 2018. Intervention: None. Measurements: Total induction bolus dose of propofol administered. Results: The mean (SD) weight‐adjusted propofol dose was 1.7 (0.6) mg/kg. The mean prevalent propofol induction dose exceeded the upper bound of what has been described as the typical geriatric dose requirement across every age category examined. The percent of patients receiving propofol induction doses above the described typical geriatric range was 64.8% (95% CI 64.6–65.0), varying from 73.8% among patients aged 65–69 to 45.8% among patients aged 80 and older. Conclusion: The present study of a large multicenter cohort demonstrates that prevalent propofol dosing commonly falls above the published typically required dose range for patients aged ≥65 in nationwide anesthetic practice. Widespread variability in induction dose administration remains incompletely explained by known patient variables. The nature and clinical consequences of these unexplained dosing decisions remain important topics for further study. Observed discordance between expected and actual induction dosing raises the question of whether there should be reconsideration of widespread provider practice or, alternatively, whether what is published as the typical propofol induction dose range should be revisited. Abstract : See related editorial by Devinney et al . in this issue.